Answer:
![f(-1) = 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3zez305buigcpzcxvya8kwonvd7ysvwfhd.png)
Explanation:
Given
f(x) =
![-x^(3)-x^(2) +1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ih5zmt8kp9l2r0z4irqjbnwzr5tcancx8k.png)
Finding f(-1) means, we have to put -1 in the places of x in the function,
So, putting x=-1 in the function
![f(-1) = (-1)^(3) - (1)^(2) +1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sm7g7swx5pmaqhqkb8dahkatdym2o75217.png)
As the power 3 is odd, the minus will remain the same, while in the 2nd term minus will be eliminated due to even power. So,
=>
![-1-1+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/llo2a8rqg99745o0lic9b84k8680kk6x1b.png)
=> 1
Hence,
![f(-1) = 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3zez305buigcpzcxvya8kwonvd7ysvwfhd.png)